Measurement of Dimensional Learning Organization Questionaire (DLOQ) at the Regional Secretariat of Palopo City - Makmur, Muhammad Ardiansyah; Akib, Haedar; Sailan, Manan (International Journal of Human Capital and Innovative Management, 2024)
This study measures the level of implementation of learning organizations using the Dimension Learning Organization Questionnaire (DLOQ) developed by Watkins and Marsick 2013 to analyze the level of implementation of DLOQ in the scope of the Palopo City regional secretariat. The approach in this study uses a quantitative research type with a descriptive method with a population of all civil servants/ASN in the Palopo City regional secretariat, namely 138 people using a saturated sampling technique, all members of the population are sampled, so in this study the number of samples is 138 people. The research instrument that has been used as a data collector in the field uses a questionnaire with 21 statement items classified into 7 dimensions by looking at three levels of implementation of learning organizations, namely individuals, units/teams and organizations. The validity technique of the questionnaire measuring instrument through the construct and content validation process until the instrument is declared valid. Furthermore, the data analysis technique uses descriptive statistics using a frequency table with a Likert scale to find the interval scale of the value criteria to highlight the percentage or frequency of respondents’ answers to the statements on the questionnaire. The results found were three levels of individual, team and organization with 21 statement items and 3 levels had an average DLOQ value of 3.28 with very appropriate criteria.